An unexpected, pH-sensitive step of the enterovirus D68 lifecycle - Aponte-Diaz, David; Vogt, Matthew R.; Cameron, Craig E. (mBio, 2023)
Enterovirus D68 (EV-D68) contributes significantly to pathogen-induced respiratory illnesses and severe neurological disorders like acute flaccid myelitis. We lack EV-D68 preventive measures, and knowledge of its molecular and cellular biology is incomplete. Multiple studies have highlighted the role of membrane compartments and autophagy during picornavirus multiplication. Galitska et al. found that EV-D68 also exploits cellular autophagic compartments and relies on autophagic machinery as pro-viral factors (G. Galitska, A. Jassey, M. A. Wagner, N. Pollack, et al., mBio e02141-23, 2023, https://doi.org/10.1128/mbio.02141-23 ). Surprisingly, failure of the autophagic compartment to acidify early during EV-D68 infection causes a delay in RNA synthesis that has not been reported for other enteroviruses. This delay appears to reflect the inability of viral proteins 2B and 3A to engage membranes stably, leading to their degradation in the cytoplasm. Observations like this underscore the importance of studying individual members of the virus genus. It will be interesting to understand how this phenomenon connects to EV-D68 pathogenesis, if at all.